Nahm data and the mass of 1/4-BPS states - HOUGHTON, CONOR JAMES (American Physical Society, 2000)
The mass of 1 / 4-BPS dyonic configurations in N=4 D=4 supersymmetric Yang-Mills theories is calculated within the Nahm formulation. The SU(3) example, with two massive monopoles and one massless monopole, is considered in detail. In this case, the massless monopole is attracted to the massive monopoles by a linear potential.
PUBLISHED
Keywords: Pure & Applied Mathematics